ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK UMUM KONVENSIONAL DAN BANK UMUM SYARIAH SEBELUM DAN SETELAH KRISIS GLOBAL 2008 - , FITRI AGUSTIN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The global financial crisis that hit the United States also spread to the rest of the world in 2008. Indonesia is a country open economy affected by the global financial crisis. Evidenced by the decline in economic growth. Based on the economic crisis in 1998, the financial performance of the banks is very influenced by the global economic crisis, including Islamic banks and conventional banks. The crisis that occurred in 1998 stated that the financial performance of Islamic banks is better than conventional banks evidenced by the number of conventional banks are insolvent at the time. Thus the purpose of this study is to prove whether the existence of the 2008 global crisis of the financial performance of Islamic banks is better than conventional banks. This study uses the CAMEL ratios that have category Capital, Assets, Management, Earnings, and Liability. This study uses quantitative methods. Begins by calculating the ratio first, then do the test for normality, when the results of the data were normally distributed test equipment used is Two Independent Sample T-Test, if not normal, used the Mann-Whitney Test for Two Independent Samples. The results showed the 2008 global crisis financial performance of Islamic banks keep better financial performance than conventional banks with Islamic CAR proved superior to the conventional mean of 28.24 compared to 14.47, Islamic NPL ratio is superior with mean 8.54 compared with conventional 3.65, the ratio is superior to Islamic NPM 15.93 compared to conventional mean of 2.05, the ratio of ROA ratio is superior to sharia mean 1.02 2.22 compared to conventional, Islamic ROA ratio is superior compared with 104.06 with conventional 84.09, and LDR sharia is superior compared to conventional 87.83 73.77.